The Future of Labour : How AI, Technological Disruption and Practice Will Change the Way We Work - Anthony Larsson; Andreas Hatzigeorgiou (Routledge, 2025)
The Future of Labour: How AI, Technological Disruption and Practice Will Change the Way We Work is an anthology that offers a forward-looking exploration of how artificial intelligence (AI), digitalisation and technological transformation are reshaping the future of work. Through a series of studies conducted by scientists and industry professionals, this volume takes a deep dive into many of the issues related to new policies, AI and the digital transformation's anticipated impact on the labour market. Balancing speculative foresight with scientific rigor, the authors ground their discussions in empirical data, theoretical frameworks, and comprehensive literature studies.The book delves into the evolving labour landscape through three key themes: The Future of Society and Economy – Examining the socio-economic implications of emerging technologies and their transformative impact on work. The Future Way of Working – Investigating how AI and digital tools are redefining the nature of work and workplace conditions. New Uses of AI and Technology in Labour – Highlighting innovative applications of AI and technology that are reshaping job roles and industries. Each chapter provides unique insights, blending rigorous analysis with predictive insights, to illuminate the challenges and opportunities of a rapidly technologically advancing labour landscape.The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 International license.